TRAIL 신호 전달과 DNA 손상 복구 반응에서 TRADD의 생리학적 기능에 관한 연구 - 구기방 (The Graduate School, Ajou University, 2017)
TNF Receptor-Associated Death Domain (TRADD) is an essential mediator of TNF receptor1 (TNFR1)-mediated TNF signaling. TRADD has a critical function in TNFR1 signaling pathway by orchestrating the formation of the TNFR1 signaling complex as well as Toll-like receptor3 (TLR3) and TLR4 signaling. The cytoplasmic functions of TRADD in death receptor signaling have been intensively studied. However, the involvement of TRADD in TNF-related apoptosis-inducing ligand (TRAIL) - and DNA damage-induced cell death is unclear. In this study, I investigated the role of TRADD in cell death induced under these two conditions. TRAIL is known to possess selective cytotoxicity towards cancer cells and therefore is considered as a promising anti-cancer therapeutic agent. One major obstacle in the clinical application of TRAIL as a cancer therapeutic agent is the acquisition of TRAIL resistance. Therefore, it is important to search for novel mechanisms underlying such resistance. In this study, I found that TRADD deficiency sensitizes cells to TRAIL-induced apoptosis. Enhanced cell death in TRADD-/- MEFs is associated with defective NF-B activation, indicating that the pro-survival function of TRADD in TRAIL signaling is mediated at least in part via NF-B activation. Consistently, siRNA knock-down of TRADD in cancer cells sensitizes them to TRAIL-induced apoptosis. Thus, our data clearly demonstrate the pro-survival role of TRADD in TRAIL signaling and targeting TRADD appears to be a logical approach in enhancing the killing effect of TRAIL and in overcoming TRAIL resistance in cancer therapy. On the other hand, it has been found that TRADD shuttles dynamically from the cytoplasm into the nucleus through its nuclear localization sequence (NLS) and nuclear export sequence (NES). However, the function of nuclear localization of TRADD remains elusive. In this study, I aimed to examine the physiological functions of TRADD in nucleus upon treatment with DNA damage agents. First, I found that TRADD deficiency increases the accumulation of double strand break (γH2AX) foci compared to wild type in response to DNA damage agent treatment. Second, I identified that DNA damage promotes translocation of TRADD from cytoplasm to the nucleus. Third, I found that nuclear localization of TRADD facilitates DNA repair through promotion of non homologous end-joining (NHEJ) repair rather than homologous recombination (HR) repair. Finally, I demonstrated that TRADD deficiency is able to sensitize MEFs to DNA damage-induced cell death through the persistent activation of JNK and accumulation of ROS. Taken together, data from this study collectively demonstrate that TRADD has a pro-survival role in TRAIL- and DNA damage- induced cell death. Thus, TRADD may be one of the key potential target for overcoming TRAIL resistance and DNA damage resistance in cancer therapy.
학위논문(박사)--아주대학교 일반대학원 :의생명과학과,2017. 2
Keywords: TRADD; TNFR1 signaling; TRAIL; DNA Repair; Cancer Cell Death